CHANGES TO STAFF TRAINING STRATEGIES IN A BUSINESS ORGANISATION IN TERMS OF LEARNING AND COMPETENCE DEVELOPMENT - Anužienė, Birutė; Zubrickienė, Ilona; Tolutienė, Gitana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This paper presents the findings of a study on attitudes of employees of business organisations towards changes in their development strategies in terms of learning and competence development. The study is based on the assumption that the lack of corporate staffs’ competences hinders innovation, impairs the quality of activities, while the engrained conventional approach towards staff training prevents from using workplace opportunities of self-study and competence development. The study identifies the following practical issue: conventional staff training, principles and methods of competence development that depend on direct and virtual learning are not always effective lately. An analysis of the research participants’ attitudes can help to answer the following problematic questions in more detail: are the acquisition of competences, trainings held, and employee learning considered identical phenomena? What is the efficiency of staff training and competence development activities or the learning tools applied? What does the application of the principles of staff training and competence development in an organisation mean in practice? The article, therefore, is aimed to analyse the changes in staff development strategies in terms of employee learning and competence development from the perspective of corporate staff.